Cooperative Integrated Reading Composition (Circ): Strategi untuk Meningkatkan Kemampuan Pemahaman Bacaan Bagi Siswa Kelas V Sekolah Dasar - Doddy Hendro Wibowo (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2016)
This study aims to determine the effectiveness of teaching methods Cooperative Integrated Reading Composition (CIRC) to improve reading comprehension ability for students of classes V Elementary School. The hypothesis of this study was difference in change ability reading of comprehension stage for fifth grade students Elementary School with the teaching methods Cooperative Integrated Reading and Composition (CIRC) and that does not use teaching methods Cooperative Integrated Reading and Composition (CIRC). The subjects were fifth grade students amount 29 students, 14 of control group students and 15 of experimental group student. Data analysis technique using Mann Whitney U test. the result obtained the value of U = 98.5, greater than a = 0.05 it can be concluded that Ho is accepted. It was concluded that there was no difference in change ability reading of comprehension stage for fifth grade students Elementary School with the teaching methods Cooperative Integrated Reading and Composition (CIRC) and that does not use teaching methods Cooperative Integrated Reading and Composition (CIRC).Â Keywords: Ability of Reading Comprehension, Learning Method Cooperative Integrated Reading and Composition (CIRC), Student Class V